Conditions and Causes for Obligation to Mitigate Damages and the Effect of Negligence in It under Iranian and German Law - Mozhdeh Jamsahar; Ebrahim Delshad Ma'aref; Seyed Mehdi Mirdadashi Kari (پژوهش های حقوق تطبیقی)
In case of breaching the contract, the injured party is entitled to receiving the compensation that places him in a status similar to full performance situation. However, if the injured party has a role to increasing the damage, either by failing to take reasonable action to mitigate the loss or by acting in a way that aggravates it, the principle of full compensation will be defected and the Amount of compensation will be regulated based on this role. This article, titled "Conditions and Causes for Obligation to Mitigate Damages and the Effect of Negligence in It under Iranian and German Law," Addresses this question that how is the scope and conditions of the injured party's obligation to mitigate and how to claim the relevant costs. Using a descriptive-analytical method and library resources, the research findings show the obligation to mitigating the damage is limited to reasonable and acceptable measures, and also substitute contract formation with a third party could fall within this framework. Moreover, the incurred costs to mitigate damages are receivable, and injured party's negligence is considered as one of the main basis to mitigate the amount of compensation.